Tissue Factor and Toll Like Receptor (TLR)4 in Hyperglycemia-Hyperinsulinemia: Effects in Healthy Subjects, and Type 1 and Type 2 Diabetes Mellitus - Singh, Anamika (Thromb Haemost, 2015)
BACKGROUND: Diabetes mellitus (DM) patients have increased cardiovascular events. Blood tissue factor-procoagulant activity (TF-PCA), the initiating mechanism for blood coagulation, is elevated in DM. We have shown that hyperglycemia (HG), hyperinsulinemia (HI) and combined HG+HI (induced using 24 hr infusion clamps) increases TF-PCA in healthy and T2DM subjects, but not in T1DM subjects. The mechanisms for this are unknown. DM patients have elevated plasma lipopolysaccharide (LPS), a toll-like receptor (TLR) 4 ligand. We postulated that TLR4 plays a role in modulating TF levels. OBJECTIVES AND METHODS: We studied the effect of HG+HI on TLR4 and TF-PCA in vivo during 24 hr HG+HI infusion clamps in healthy subjects, and T1DM and T2DM subjects, and in vitro in blood. RESULTS: In vivo, in healthy subjects, 24 hr HG + HI infusion increased TLR4 6-fold, which correlated with TF-PCA (r= 0.91, p<0.0001). T2DM patients showed smaller increases in both. In T1DM subjects, TLR4 declined (50%, p<0.05) and correlated with TF-PCA (r=0.55; p<0.05). In vitro, HG (200 mg/dl added glucose) and HI (1-100 nM added insulin) increased TF-PCA in healthy subjects (~2-fold, 2-4 hr). Insulin inhibited by ~30% LPS-induced increase in TF-PCA and high glucose reversed it. TLR4 levels paralleled TF-PCA (r=0.71, p<0.0001); HG and HI increased TLR4 and insulin inhibited LPS-induced TLR4 increase. CONCLUSIONS: This is first evidence that even in healthy subjects, HG of short duration increases TLR4 and TF-PCA, key players in inflammation and thrombosis. TLR4-TF interplay is strikingly different in non-diabetic, T1DM and T2DM subjects.